The aggravated vulnerability of children in the face of advertising activity: case of “dream animals” (Research, Society and Development, 2020)
The content covered has as its main basis to analyze, taking as a parameter the case "BICHINHOS DOS SONHOS", the influence exercised by advertising in marketing decisions by the child audience, as well as verifying the protection conferred by the Consumer Protection Code (CDC) to the childish consumer. In this perspective, this article, through exploratory research, of a qualitative nature, inductive method, collection of documentary and bibliographic data, proceeded in order to verify the evolution of the children's market, aiming to analyze how the infant was inserted in a consumerist reality, becoming a potential consumer. Nevertheless, it also elucidated the way in which the advertising market reacted in the face of such evolution, especially with regard to the development of strategies capable of influencing children in decision-making. In this way, the Law could not deviate from the responsibility of guaranteeing infants their rights. Thus, the CDC, in order to protect the child consumer, started to consider the child as a being in a condition of aggravated vulnerability in the face of the consumption relationship, considering the young age and because they are still in the process of biopsychological development. Finally, in view of the exposed problem, it was sought, based on the principle of comprehensive protection, to outline mechanisms capable of ensuring that the child, through the family, society and the State, fully develops.